PERAN UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES DALAM MENANGANI PENCARI SUAKA AFGANISTAN DI PEKANBARU (INDONESIA) TAHUN 2015 ( Studi Kasus: Pencari Suaka Afganistan di Rumah Detensi Imigrasi Pekanbaru) - Wulandari, Anggita; Fachri, Yuli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
study analyzes the role of the United Nations made High Commissioner for Refugees in dealing with asylum seekers Afghan in Pekanbaru-Indonesia 2015 with the focus of research that Afghan asylum seekers in immigration detention of Pekanbaru.This research method is library research and interviews. The framework used by the author is Level of Analysis used International Organization ,International Organization Theory and Theory of Roles, human security concept and perspective neoliberalis.From the analysis using the concepts and theories and perspectives, we can conclude that as an international organization under the auspices of the United Nations tasked to deal with the problem of refugees, the UNHCR exercised its powers in dealing with asylum seekers who are in immigration detention Pekanbaru by doing data collection to Rudenim though not scheduled and rated slow. After UNHCR to collect data then after that every Deteni given a registration number to the end of his interview to determine their statusnya.if declared as refugees then these people moved into camps under the supervision of Class I Immigration Office Pekanbaru and that has not been given the status the refugees must remain in Detention Centre of Pekanbaru during the process. UNHCR also helps asylum seekers / Refugees to obtain a durable solution is local integration, pengembalia voluntary and third country resettlement. However, UNHCR has not been able to carry out its role with maximum because hampered by the lack of shelter provided to asylum-finding / pegungsi and lack of operational funds.Keywords: UNHCR, Asylum Seekers. Refugees, Afghanistan, Detention Imigration of Pekanbaru.